MENAKAR SISI PRAGMATISME KAUM SANTRI: PERGESERAN CARA PANDANG SANTRI TERHADAP PENDIDIKAN ISLAM DI PONDOK PESANTREN DI KOTA KEDIRI - Ainul Naim (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2019)
Transformation of Islamic Boarding School (well-known as Pesantren) toward the modernity is undeniable choice in order to preserve it existence in the contemporary era. Thus, the decision of Kyai (as the prime leader of Pesantren) to adopt and to synchronize the curriculum of Pesantren may effect on the shift of sub-culture and the orientation of santri on the Islamic education. This research are focus on three significant issues: Firstly, Mapping of Santri’s Sub-Culture perspective on the modernity in Pesantren; Secondly, Analyzing of The Shifting of Santri’s perception on modernity, Thirdly, Elaborating The Challenges and Opportunities of Pesantren in the modernity. This research isconducted in several pesantren which adopted modernization locates in Kediri, East Java.This study uses a critical paradigm, a qualitative approach and a case study strategy. Collecting the data throughin-depth interview method, field observation and documentating from santri and kyai’s responses from each pesantren